Interorganizational Cooperation and Youth Policy: Case of Utena - Vaičiūnaitė, Gerda; Dunajevas, Eugenijus (Politologija, 2019)
The implementation of youth policy is closely connected to interorganizational cooperation between the organizations that are active in the field of youth activities. The goal of this paper is to present the results of a study wherein the factors that possibly determine cooperation between youth organizations and the local government administration in the Utena District municipality were studied. According to the studies on cooperation and organizational behavior, the factors that contribute to cooperation are the following: an uncertainty of the future, possessing mutual goals, the costs and benefits of cooperation maintenance, and the level of trust between organizations. In order to determine the exact combination of factors and how they contribute to cross-organizational cooperation, a crisp-set qualitative comparative analysis was conducted. The possible cooperation situations between the organizations that are active in the field of youth and the local government administration were the study cases. The semistructured interview method was employed in order to interview the representatives of local the government administration and organizations. The results of data analysis revealed that the most important factor for interorganizational cooperation in the field of youth policy is the level of trust between organizations in the Utena District municipality.
Keywords: cooperation; youth policy; qualitative comparative analysis; Utena